2023
DOI: 10.1001/jama.2023.19521
|View full text |Cite
|
Sign up to set email alerts
|

US Medical Student Plans to Practice in Underserved Areas

Liselotte N. Dyrbye,
Danielle E. Brushaber,
Colin P. West

Abstract: This study explores US medical students’ intent to practice in underserved areas, analyzed by demographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The results confirm that racially and ethnically minoritized medical students have stronger intentions to practice in underserved areas, but the analysis then links these intentions with the much needed and continued diversification of the medical workforce. The authors imply that to meet the needs of underserved areas, more racially and ethnically minoritized medical students must be recruited into the medical pipeline.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The results confirm that racially and ethnically minoritized medical students have stronger intentions to practice in underserved areas, but the analysis then links these intentions with the much needed and continued diversification of the medical workforce. The authors imply that to meet the needs of underserved areas, more racially and ethnically minoritized medical students must be recruited into the medical pipeline.…”
mentioning
confidence: 61%
“…To the Editor The research letter by Dyrbye and colleagues explored US medical student plans to practice in underserved areas and further disaggregated how racially and ethnically minoritized medical students might address the physician workforce shortage in these areas.…”
mentioning
confidence: 99%
“…In our study of 45 687 graduating medical students, those who identified as female; bisexual, gay, or lesbian; American Indian or Alaska Native; Black or African American; Hispanic, Latino, or of Spanish origin; and Native Hawaiian or Other Pacific Islander had higher odds of intent to practice in underserved areas than those who did not identify with any of these groups …”
mentioning
confidence: 74%
“…In Reply We appreciate the thoughtful comments from Mr Akimoto and colleagues and Dr Soh regarding our recently published study . We wish to clarify that we did not state nor did we intend to imply that any specific demographic of physicians is uniquely responsible for caring for patients in underserved areas.…”
mentioning
confidence: 96%
“…To the Editor A recent research letter by Dyrbye and colleagues evaluated medical students’ intent to practice in underserved areas by race, ethnicity, sex, and sexual orientation between 2019 and 2021. Dyrbye and colleagues found that American Indian or Alaska Native; Black or African American; Hispanic, Latino, or of Spanish origin; and Native Hawaiian or Other Pacific Islander medical students were significantly more likely to report intent to practice in underserved areas. As Native Hawaiian or Other Pacific Islander physicians and researchers, we commend the authors on abiding by federal race standards, including Indigenous students, and offer further context to these findings …”
mentioning
confidence: 99%